Integrasi Teknologi dan Sektor Pendidikan: Tantangan dan Peluang dalam Perspektif Multisektoral - Judijanto, Loso; Rengga Yudha Santoso; Mansur, Ali (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
Technology integration is the process of unifying or combining various components of information and communication technology into a system or operation to improve efficiency, effectiveness, and performance. This integration includes various aspects, such as hardware, software, network infrastructure, and data. The study in this research uses the literature method. The results show that technology integration in the education sector presents significant challenges and opportunities in addressing 21st century learning needs. In this process, various obstacles such as gaps in access to technological infrastructure, limited teacher competence, and data security and privacy issues emerge as critical issues that need serious handling. However, technology also opens up great opportunities to improve the quality and reach of education through distance learning, higher interactivity, and personalisation of the teaching and learning process. A multi-sectoral approach involving the government, private sector, educational institutions and communities is needed to overcome these challenges and maximise the benefits. With effective collaboration, it is hoped that technology integration can create an education system that is more adaptive, inclusive and responsive to global dynamics.